End-tidal carbon dioxide monitoring improves patient safety during propofol-based sedation for breast lumpectomy: A randomised controlled trial. Issue 11 (November 2018) - Li, Mengzhu; Liu, Zhiqiang; Lin, Fuqing; Wang, Huiying; Niu, Xiaozhen; Ge, Xun; Fu, Shukun; Fang, Lin; Li, Cheng
Abstract : BACKGROUND: The use of sedation is becoming more commonplace. Although pulse oximetry is a standard monitoring procedure during sedation, it cannot accurately detect early hypoventilation. End-tidal carbon dioxide (EtCO2 ) monitoring can be an earlier indicator of airway compromise; however, the existing literature is limited to a few studies with varying outcomes. OBJECTIVES: To evaluate whether EtCO2 monitoring decreases the incidences of CO2 retention and apnoeic events in propofol-based sedation. DESIGN: Randomised controlled study. SETTING: A tertiary hospital. PATIENTS: Two hundred women (aged 18 to 65 years, ASA physical status 1 or 2) who were scheduled for breast lumpectomy between June 2017 and August 2017. INTERVENTIONS: Patients were allocated randomly to receive either standard monitoring or standard monitoring and EtCO2 monitoring. MAIN OUTCOME MEASURES: The primary outcome was the incidence of CO2 retention. The secondary outcomes were the number of actions taken to restore ventilation, variations in P a CO2 and pH, the frequency of apnoea and the recovery time. RESULTS: CO2 retention occurred significantly less often in the EtCO2 monitoring group (10 vs. 87%; P < 0.0001). In the standard monitoring group, the mean P a CO2 was more than 6 kPa (45 mmHg) and the pH was less than 7.35 at 5, 10, 20 and 30 min after induction of anaesthesia and at the end of the procedure. Both values were within the normal range in the EtCO2 monitoring group. The number of airway interventions performed was significantly higher in the EtCO2 monitoring group (9.8 ± 1.8 vs. 1.9 ± 1.0; P < 0.0001). Apnoea occurred significantly less often in the EtCO2 monitoring group (0 vs. 10%; P < 0.0001) and recovery time was shorter (9.9 ± 1.4 vs. 11.4 ± 2.1 min; P = 0.048). CONCLUSION: The addition of EtCO2 monitoring to standard monitoring during propofol-based sedation can improve patient safety by decreasing the incidence of CO2 retention, and therefore the risk of hypoxaemia through early recognition of apnoea, and can also shorten recovery time. TRIAL REGISTRATION: This trial is registered withhttp://www.chictr.org.cn (ChiCTR-INR-17011537).